2020
DOI: 10.1021/acs.energyfuels.0c03193
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance and Stability of the Co-anaerobic Digestion of Municipal Sludge and Food Waste by Granular Activated Carbon Dosing

Abstract: This study investigated the effects of granular activated carbon (GAC) dosing on the co-anaerobic digestion of municipal sludge and food waste. It was found that methane production increased in the GAC systems. The cumulative methane production in the 1 g·L–1 GAC system was 12.14% higher than the control. The 1 g·L–1 GAC system started very quickly at the initial stage of anaerobic digestion (AD) and reached the highest methane production per day on the 3rd day, while the control appeared on the 10th day. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The increase was attributed to enhanced DIET because of the enrichment of Geobacter and Methanobacterium on the surface of GAC. A 12.14% increase in biomethane production by GAC on food waste treatment was reported [59], where DIET participant Geobacter increased close to an order of magnitude. Enhancement of biomethane performance by GAC with Geobacter was found somewhere else, where 49.8% of the organisms on the surface of GAC were Geobacter species [60].…”
Section: Promoting Interspecies Electron Transfer Efficiencymentioning
confidence: 92%
See 1 more Smart Citation
“…The increase was attributed to enhanced DIET because of the enrichment of Geobacter and Methanobacterium on the surface of GAC. A 12.14% increase in biomethane production by GAC on food waste treatment was reported [59], where DIET participant Geobacter increased close to an order of magnitude. Enhancement of biomethane performance by GAC with Geobacter was found somewhere else, where 49.8% of the organisms on the surface of GAC were Geobacter species [60].…”
Section: Promoting Interspecies Electron Transfer Efficiencymentioning
confidence: 92%
“…GAC can serve as a pH buffer because of its high adsorption capacity of VFAs and simultaneously promote the degradation of VFAs, thus stabilizing the pH variations and enhancing substrate production for methanogens. Wang et al demonstrated that 1 g⋅L -1 GAC in the AD system effectively stabilized the pH value, resulting in a 12% increase of methane production and reduced AD start-up time by about 5 days [59]. The pH buffering capacity of GAC was also observed at a concentration up to 20 g⋅L -1 , which showed the best performance that enhanced the methane production by 27% [97].…”
Section: Ph Regulationmentioning
confidence: 99%
“…(2008) operated an expanded granular sludge bed reactor packed with GAC at high volumetric organic loading to produce hydrogen from molasses-containing wastewater and showed high hydrogen production with better operational stability at a shorter fermentation time. Similarly, Wang et al (2020) reported 12.14% higher methane production by using GAC as a support media in anaerobic co-digestion of municipal sludge and food waste.…”
Section: Gac For Lbr Operation At High Volumetric Organic Loadingmentioning
confidence: 93%
“…GAC can be derived by pyrolysis of the organic waste biomass with low production costs. Research studies have also reported the positive impact of GAC as a support media for microbial attachment in anaerobic bioreactors producing hydrogen, and methane (Bertin et al, 2010;Lutpi et al, 2015;Mohan et al, 2008;Guo et al, 2008;Wang et al, 2020). For example, Guo et al…”
Section: Gac For Lbr Operation At High Volumetric Organic Loadingmentioning
confidence: 99%